Giới hạn quyền tác giả trong hoạt động giảng dạy, nghiên cứu khoa học theo pháp luật về sở hữu trí tuệ Việt Nam - Quyền sao chép của thư viện - Nguyễn, Khánh Phương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
In the educational environment, libraries play an important role in providing information sources to support teaching and research activities. Aiming to reserve and enforce the right of access to information of each individual in society and while demonstrating that the library's functions are rightfully performed, Intellectual Property Law of Vietnam has recognized the library's reproduction right as one of the limitations of copyright. This also indicates the balance between the interest of the author, the copyright holder and that of the community; thus, contributing to the overall development of society.